2020
DOI: 10.1093/qje/qjaa027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Police Violence on Inner-City Students*

Abstract: Nearly a thousand officer-involved killings occur each year in the United States. This paper documents the large, racially disparate impacts of these events on the educational and psychological well-being of Los Angeles public high school students. Exploiting hyperlocal variation in how close students live to a killing, I find that exposure to police violence leads to persistent decreases in GPA, increased incidence of emotional disturbance, and lower rates of high school completion and college enrollment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 73 publications
5
92
0
2
Order By: Relevance
“…Yet other factors have not been included as measured covariates and so may constitute potential confounds. Examples include exposure to lead or air pollution, violence in the home or neighborhood, and maternal depression, which are associated with both disability identification (e.g., Ang, 2020; McGuinn et al, 2020; Rogers et al, 2020; Sioen et al, 2013) and race or ethnicity (e.g., Chan et al, 2020; Sheats et al, 2018; Tessum et al, 2019). Methodologically, omitted variable bias due to unmeasured confounding is possible.…”
Section: The Importance Of Assessing For Unmeasured Confounding In Studies Reporting Disability Under-identificationmentioning
confidence: 99%
“…Yet other factors have not been included as measured covariates and so may constitute potential confounds. Examples include exposure to lead or air pollution, violence in the home or neighborhood, and maternal depression, which are associated with both disability identification (e.g., Ang, 2020; McGuinn et al, 2020; Rogers et al, 2020; Sioen et al, 2013) and race or ethnicity (e.g., Chan et al, 2020; Sheats et al, 2018; Tessum et al, 2019). Methodologically, omitted variable bias due to unmeasured confounding is possible.…”
Section: The Importance Of Assessing For Unmeasured Confounding In Studies Reporting Disability Under-identificationmentioning
confidence: 99%
“…First, most research on the link between the criminal justice system and child development focuses on parental incarceration, even though law enforcement and policing are a central, and the most visible, part of the criminal justice system. Second, important research has examined the consequences of police stops and arrests for mental health (Geller et al 2014;Sugie and Turney 2017), system avoidance (Brayne 2014), political participation (Lerman and Weaver 2014), and other outcomes, but the potential consequences of policing for youth have largely been ignored (for exceptions, see Ang 2018;Fagan and Tyler 2005;Kirk and Sampson 2013). Juveniles are of particular interest for understanding the link between the criminal justice system and social inequality.…”
Section: Policing Crime and Educational Outcomesmentioning
confidence: 99%
“…They propose that general anxiety and fear simply based on seeing police officers or observing police intrusions on neighbors, friends, and family members explain part of this effect. Other research documents how police killings have spillover effects on the mental health of Black Americans (Ang 2018;Bor et al 2018). Many of these findings are limited by the cross-sectional nature of the data, but they suggest health consequences related to stress, fear, trauma, and anxiety might affect entire communities and not only individuals in contact with the police and the criminal justice system.…”
Section: Aggressive Policing and The Educational Performance Of Minormentioning
confidence: 99%
“…The detrimental effects of these high-profile police killing incidents are likely more severe and long lasting than what has been documented. Using the data from a large urban district in the Southwest, Ang (2020) demonstrated that police killings, even those that go unreported in the media, caused immediate spikes in absenteeism, decreases in grade point averages, and increased emotional disturbance for high school students who lived close to the site of the events. In addition, these negative effects were greatest for Black and Hispanic students and persisted for several years, as reflected by lower high school graduation and college enrollment rates among students who were ninth graders when the police killings happened.…”
Section: Introductionmentioning
confidence: 99%